Oblog cardboard furniture : the exploration of cardboard for bench design - Abdullah Sani, Mohd Najib; Ab Aziz, Nurul Husna (2016)
Using waste cardboard based from recycled paper to design indoor furniture. Proposed the design of cardboard sitting bench. Layers of cardboard were stacked, glued and cut into shape and thickness of a bench. Promote sustainability in product design.